2022
DOI: 10.5781/jwj.2022.40.5.7
|View full text |Cite
|
Sign up to set email alerts
|

Study on Laser Welding of Dissimilar Materials between Aluminum and Copper (Ⅰ) - Research Trend in Laser Welding Technology and Materials Testing Methods -

Abstract: In the rapidly changing automobile market, the important issues in assembling electric vehicles (EVs) can be summarized as weight reduction and battery safety. For the battery manufacturing technology, welding of dissimilar materials is crucial to assure the functionality and reliability of the battery systems installed in the recently developed EVs. This paper discusses research trends in laser welding technology for joining Al and Cu, which is currently applied for the joining process in the battery pack man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 49 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Upon observing the cross-sections of the weld joints, no cracks were observed, but porosity was detected at the interface on the Al side. It is assumed that the fast welding speed and solidification speed, characteristic of laser welding, prevented hydrogen emission, resulting in porosity at the interface [18]. Additionally, it was confirmed that the higher amount of upper sheet Al melting was due to the different melting points of the two base materials [16,17].…”
Section: Bead Profiles According To Pitchesmentioning
confidence: 91%
“…Upon observing the cross-sections of the weld joints, no cracks were observed, but porosity was detected at the interface on the Al side. It is assumed that the fast welding speed and solidification speed, characteristic of laser welding, prevented hydrogen emission, resulting in porosity at the interface [18]. Additionally, it was confirmed that the higher amount of upper sheet Al melting was due to the different melting points of the two base materials [16,17].…”
Section: Bead Profiles According To Pitchesmentioning
confidence: 91%